2008
DOI: 10.1016/j.diamond.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

785 nm Raman spectroscopy of CVD diamond films

Abstract: Raman spectroscopy is a powerful technique often used to study CVD diamond films, however, very little work has been reported for the Raman study of CVD diamond films using near infrared (785 nm) excitation. Here, we report that when using 785 nm excitation, the Raman spectra from thin polycrystalline diamond films exhibit a multitude of peaks (over 30) ranging from 400-3000 cm-1. These features are too sharp to be photoluminescence, and are a function of film thickness. For films >30 µm thick, freestanding fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
3
11
0
7
Order By: Relevance
“…This proves that the implanted layer is free from graphitic bonds which is in agreement with the study as reported in [13]. The first and second order of Silicon substrate Raman peaks are found at the wave number 500 and 1000 cm -1 as corfirmed by May et al [14]. Asymmetry peak profile at wave number 1120 cm -1 may be related to the Fano lineshape due to quantum mechanical interference induced by boron dopant as reported in [15] and this Fano interference effects were much reduced for the smaller grain sized.…”
Section: Raman Spectroscopysupporting
confidence: 80%
“…This proves that the implanted layer is free from graphitic bonds which is in agreement with the study as reported in [13]. The first and second order of Silicon substrate Raman peaks are found at the wave number 500 and 1000 cm -1 as corfirmed by May et al [14]. Asymmetry peak profile at wave number 1120 cm -1 may be related to the Fano lineshape due to quantum mechanical interference induced by boron dopant as reported in [15] and this Fano interference effects were much reduced for the smaller grain sized.…”
Section: Raman Spectroscopysupporting
confidence: 80%
“…P. W. May et al related peaks in the range of 1459 cm −1 to 1465 cm −1 to trans-polyacetylene. 20 The results presented in this work have demonstrated that it is possible to deposit a mixture of amorphous carbon, graphite, DLC, microdiamond and nanodiamond on silicon substrates with low voltage and close to room temperature. The structures deposited have been of non-homogeneous films and with low deposition rates, of around 0.1 μm.h −1 .…”
Section: Resultsmentioning
confidence: 79%
“…Ferrari & Robertson (2001) assigned both peaks to transpolyacetylene at grain boundaries and surfaces of nanodiamonds. The weak peak at ∼1020 cm −1 along with the broad feature centered at ∼1270 cm −1 are also associated with nanodiamonds (Veres et al 2007;May et al 2008), and the broad doublet at ∼1800 and 1900 cm −1 may be due to overtones and/or combinations. In the 2000-4000 cm −1 region (not shown), the Raman spectra show broad CH-stretching peaks centered at ∼2900 cm −1 in Figure 1.…”
Section: Raman Spectroscopymentioning
confidence: 99%